SRH Recombination Strength of Interstitial Iron in Solar Grade Silicon - Rahman, Mohammad Ziaur; Alam, Mohammad Jahangir (Photonics Letters of Poland, 2013)
Shockley-Read-Hall (SRH) recombination is the main determinant for the effective minority carrier lifetime in silicon. This research has focused on the study to find the recombination strength of interstitial iron on low injection Shockley-Read-Hall recombination in compensated solar grade silicon by means of analytical modelling. This study found that strength of iron in SRH recombination is depends on the doping concentration and symmetry of minority carrier capture cross-section. This study shows that iron become more recombination active at higher doping and at lower symmetry of capture cross-section. Full Text: PDF References A.A. Istratov, T. Buonassisi, R.J. McDonald, A.R. Smith, R.Schindler, J.A. Rand, J.P. Kalejs, and E.R. Weber, "Metal content of multicrystalline silicon for solar cells and its impact on minority carrier diffusion length", J. Appl. Phys. 94, 6552 (2003). CrossRef T. Buonassisi, M.A. Marcus, A.A. Istratov, M. Heuer, T.F. Ciszek, B. Lai, C. Zhonghou, and E.R. Weber, "Analysis of copper-rich precipitates in silicon: Chemical state, gettering, and impact on multicrystalline silicon solar cell material", J. Appl. Phys. 97, 63503 (2005). CrossRef T. Buonassisi, A.A. Istratov, M. Heuer, M.A. Marcus, R. Jonczyk, J. Isenberg, B. Lai, C. Zhonghou, S. Heald, W. Warta, R. Schindler, G. Willeke, and E.R. Weber, "Synchrotron-based investigations of the nature and impact of iron contamination in multicrystalline silicon solar cells", J. Appl. Phys. 97, 74901 (2005). CrossRef T. Buonassisi et al., "Chemical natures and distributions of metal impurities in multicrystalline silicon materials", Prog. Photovolt: Res. Appl. 14, 513?531 (2006). CrossRef T. Buonassisi, A.A. Istratov, M.D. Pickett, J.P. Rakotoniaina, O. Breitenstein,M.A. Marcus, S.M. Heald, and E.R. Weber, "Transition metals in photovoltaic-grade ingot-cast multicrystalline silicon: Assessing the role of impurities in silicon nitride crucible lining material", Journal of Crystal Growth 287, 402?407 (2006). CrossRef A.A. Istratov, H. Hieslmair, and E. R. Weber, "Iron and its complexes in silicon", Appl. Phys A: Material Science and Processing 69, 13 ? 44 (1999). CrossRef D. Macdonald, PhD thesis, Australian National University (2001). K. Graff, "Metal impurities in silicon-device fabrication", Springer-Verlag, Berlin (1995). CrossRef R . Hall, "Electron-Hole Recombination in Germanium", Physics Review 87, 387 (1952). CrossRef W. Shockley and W. Read, "Statistics of the Recombinations of Holes and Electrons", Physical Rev.87, 835-842 (1952). CrossRef Y. Yoon, B. Paudyal, J. Kim, Y. Ok, and P. Kulshreshtha, "Effect of nickel contamination on high carrier lifetime n-type crystalline silicon", Journal of Applied Physics 111, 033702 (2012). CrossRef Libal J. et al, "Effect of compensation and of metallic impurities on the electrical properties of Cz-grown solar grade silicon", Journal of Applied Physics 104, 10450 (2008). CrossRef M. Ziaur Rahman and M. Jahangir Alam, "Enhancement of Minority Carrier Lifetime of Fe Contaminated Boron-Phosphorus Compensated p-Type SoG Silicon", Photonics Letters of Poland 5(2), 75 ? 77 (2013) DirectLink D. K. Schroder, American Society for Testing and Materials, ASTM STP 1340, 1998. J. Schmidt, C. Berge, A.G. ABerle, "Injection level dependence of the defect-related carrier lifetime in light-degraded boron-doped Czochralski silicon", Appl. Phys. Lett. 73 (15), 2167-9 (1998). CrossRef M. Ichimura et al., "Temperature Dependence of Carrier Recombination Lifetime in Si Wafers", J. Electrochem. Soc. 145 (9), 3265 ? 71 (1998). CrossRef